Whole Genome Sequencing Reveals Genetic Differences Between Symbiodiniaceae Populations Among Reproductively and Geographically Isolated Acropora Colonies in Western Australia - Sanna Y. Eriksson; Mikhail V. Matz; Peter D. Vize; Natalie L. Rosser (Ecology and Evolution)
ABSTRACT Significant genetic differentiation between Symbiodiniaceae populations in coral hosts can be induced by a range of factors including geography, latitude, depth, temperature and light utilisation. The conventional method of measuring Symbiodiniaceae diversity involving the ITS2 region of rDNA has several limitations, stemming from insufficient genetic resolution and the multi‐copy nature of the marker. This could be improved by using higher throughput whole genome sequencing to identify fine‐scale population genetic differences and provide new insight into factors influencing coral‐Symbiodiniaceae associations. The aim of this study was to investigate the genetic diversity of Symbiodiniaceae populations using low‐coverage whole genome sequencing in sympatric populations of Acropora cf. secale and allopatric populations of Acropora millepora that reproduce in different seasons in Western Australia. Genetic diversity of Symbiodiniaceae populations in these two species was examined using principal coordinates analysis and permutational analysis of variance. This analysis revealed that while all colonies were dominated by Cladocopium, there was a significant genetic difference between Symbiodiniaceae populations in both species. In A. millepora, this variation could be due to the latitudinal variation between populations or differences in reproductive seasonality, but in sympatric populations of A. cf. secale, genetic differences between Symbiodiniaceae populations were clearly aligned with the reproductive seasonality of the coral host. The use of whole genome sequencing improved the sensitivity to detect Symbiodiniaceae genetic population structure between coral populations, which increases our ability to identify genetic and potentially functional differences associated with variation in Symbiodiniaceae populations.